PENGARUH PROMOSI DAN LOKASI TERHADAP KEPUASAN KONSUMEN PADA PENJUALAN MIE BASUDARA - Refando Kumampung; Harifudin Thahir (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2024)
This research is motivated by the importance of increasing customer satisfaction because in a business like Mie Basudara it is required to be able to meet the needs of its consumers, so that customers who come to buy get satisfaction. Considering that customer satisfaction is an absolute requirement to survive as proof of the company's survival. This study aims to determine the effect of promotion on customer satisfaction, the effect of location on customer satisfaction, the effect of location and promotion together on customer satisfaction. This study aims to test and analyze the effect of promotion and location on customer satisfaction. Based on the results of interviews, this sales location is indeed a good location because it is easily accessible to Mie Basudara consumers, because the selling location for Basudara Noodles is in the Masomba market, Palu city. Based on the interview results, research results and the author's interpretation, sales promotion and location simultaneously have a significant effect on purchasing decisions, sales promotions partially have a significant effect on purchasing decisions at Mie Basudara. Location influences the purchasing decision. Mie Basudara has understood the importance of marketing strategy and has implemented several marketing strategies to increase sales.